Risk-type and preference-based selection and stability of funeral insurance associations in Thailand - Juliane Zenker; Tabea Herrmann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Funeral Aid Associations (FAAs) in Northeast Thailand offer micro funeral insurance at affordable premium levels while they barely risk-rate potential members. Due to the set-up of FAAs, high-risk individuals have a monetary incentive to join the insurance. Compared to many other micro insurance schemes, however, FAAs do not seem to face adverse effects of this unregulated selection of high-risk individuals into the schemes. We show that this is partly due to a counter-balancing selection of a sufficient number of low-risk individuals, who deliberately buy insurance despite what their risk types would advice. This is particularly the case for married individuals who self-select into the associations at relatively lower risks. We provide a theoretical framework showing that marriage may reduce mortality risk and at the same time increase insurance demand based on altruistic tendencies towards the spouse. Our results suggest that this preference based selection is able to balance 13 percent of the high-risk type selection based on age, health, and gender.
Keywords: D14; D82; G22; 330